Analisis Gerak Tari Sentak Baindang di Sanggar Tuah Sakato Kecamatan Pauh Kota Padang - Alya Putri; Herlinda Mansyur (SENDRATASIK UNP, 2023)
This research aims to reveal and describe the movement analysis of the Sentak  Baindang Dance at Sanggar Tuah Sakato, Pauh District, Padang City. The type of research used is qualitative research with descriptive methods. The instrument for this research is the researcher himself and is assisted by supporting instruments such as writing equipment and a camera. The data in this research uses primary data and secondary data. Data collection techniques were carried out using literature study, observation, interviews and documentation. The steps for analyzing data are data collection, data reduction, data presentation and concluding. The results of the research show that the Sentak Baindang Dance at Sanggar Tuah Sakato is a new dance creation. The Sentak Baindang Dance can be viewed from the aspects of space, time and energy. The Sentak Baindang Dance has 28 kinds of movements. From the aspect of space, it has elements of line, volume, facing direction and focus of view. The lines in this dance are predominantly straight, curved and angular lines. The volumes contained in this dance are predominantly large, medium and small. The facing directions in this dance movement are dominantly front, right and left diagonal, right and left side. The levels contained in the Sentak Baindang Dance movements are dominantly large, medium and small. The focus of view in this dance movement is dominant towards the hands, the property being held, the right and left sides, right and left diagonally. From the time aspect, the dominant tempo and rhythm are medium and fast. Meanwhile, the aspect of energy and intensity in this dance movement is dominantly medium and strong, the pressure in this dance movement is dominantly strong and the quality of the Baindang Sentak Dance movement is dominantly medium and firm.